2018
DOI: 10.1039/c8cc07632d
|View full text |Cite
|
Sign up to set email alerts
|

Taming a silyldiium cation and its reactivity towards sodium phosphaethynolate

Abstract: The synthesis of a (bis)NHC-silyldiium cation is reported and its reactivity towards sodium phosphaethynolate is shown to enable access to seven-membered heterocycles with P–X moieties (X = Si, P).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
11
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 39 publications
2
11
0
1
Order By: Relevance
“…[5,6] Other silicon(IV)based LAs are routinely used in organic synthesis, with the commercially available TMSOTf (TMS = Me 3 Si) arguably being prevalent, [7] but far from being a LSA. [3] Bis-and tris(triflate) silanes potentially represent stronger LAs, but have mainly served as building blocks for polysilane syntheses [8,9] or as precursors for silicon-based polycations [10,11] with cleavage of the SiÀOTf bonds. Donor-free Si(OTf) 4 has not been isolated to date, [9] but recently, a high FIA was calculated for Si(OTf) 4 suggesting its Lewis superacidity.…”
mentioning
confidence: 99%
“…[5,6] Other silicon(IV)based LAs are routinely used in organic synthesis, with the commercially available TMSOTf (TMS = Me 3 Si) arguably being prevalent, [7] but far from being a LSA. [3] Bis-and tris(triflate) silanes potentially represent stronger LAs, but have mainly served as building blocks for polysilane syntheses [8,9] or as precursors for silicon-based polycations [10,11] with cleavage of the SiÀOTf bonds. Donor-free Si(OTf) 4 has not been isolated to date, [9] but recently, a high FIA was calculated for Si(OTf) 4 suggesting its Lewis superacidity.…”
mentioning
confidence: 99%
“…In some exceptional cases, the oxophilicity of the metal ion can instead deoxygenate [PCO] − , thus affording the metal‐oxide and cyaphide (CP − ) as the final fragments [10] . [PCO] − can also deliver a phosphorus atom to various electrophilic organic moieties, such as imidazolium, [11] silyldiium, [12] cyclopropenium, [13] chlorodiazaphospholidine, [14] cyclotrisilenes, [15] boroles, [16] and acyl chlorides, [17] inter alia [18] . Likewise, unsaturated organic molecules can engage the [PCO] − anion to give cyclooligomerizations that produce P‐containing heterocycles, [19] wherein the reaction generally proceeds through [2+2], [3+2], or [4+2] cycloaddition pathways [19f] …”
Section: Methodsmentioning
confidence: 99%
“…In 2018, Driess and co-workers reported the synthesis of a novel dicationic bis(NHC)-stabilised silyldiium complex ( 46 ; bis(NHC) = [CH 2 (NC 3 H 2 NDipp) 2 ], Dipp = 2,6- i Pr 2 C 6 H 3 ) by the reaction of Ph 2 Si(OTf) 2 with bis(NHC) in 1 : 1 molar ratio (Scheme 18b). 56 The 29 Si NMR of 4-coordinated Si appeared at δ = −36.7 ppm. The structure of 46 was rationalized by SCXRD analysis, which revealed that triflate anions and the central Si atom have no close contact.…”
Section: Reactivity Of Ocp− Towards Main-group Elementsmentioning
confidence: 99%